Safety culture regarding zoonoses on domestic ruminant farms - Starič, Jože; Hodnik, Jaka Jakob; Drusany Starič, Kristina; Ježek, Jožica; Janev Holcer, Nataša; Leppälä, Jarkko; Rautiainen, Risto (2020)
Veterinarians in buiatric practice, alongside veterinary care and animal welfare, are also responsible for protecting assisting personnel and those working on the holding from zoonoses. Therefore, they need to be knowledgeable about common zoonotic diseases of ruminants, in particular, and protection from their contraction. Veterinarians should know which zoonotic diseases are present in their country and neighbouring countries to be prepared to advise. Zoonotic diseases of ruminants often show no typical clinical presentation, so awareness of self-protective behaviour when dealing with animals in the prevention of zoonoses is very important. This article provides a review of the common zoonoses of domestic ruminants in South-East Europe that are transmitted when handling animals, and their manner of transmission to humans. Safety culture in ruminant production relates to employee attitudes and behaviour concerning health and safety, which also has a significant impact on zoonosis prevention. Improving the safety culture among livestock sector workers and worker behaviours that prevent the risk of zoonoses are also discussed.
Veterinari su u buiatričkoj praksi, uz veterinarsku skrb i dobrobit životinja, odgovorni i za zaštitu pomoćnog osoblja i osoblja koje radi na gospodarstvima od zoonoza. Stoga trebaju posjedovati znanje o uobičajenim zoonotskim bolestima preživača, posebno o zaštiti od obolijevanja od takvih bolesti. Veterinari bi trebali znati koje su zoonotske bolesti prisutne u njihovoj, kao i u susjednim zemljama kako bi bili spremni savjetovati osoblje na gospodarstvima. Zoonotske bolesti preživača često ne pokazuju nikakve tipične kliničke znakove, stoga je svijest o ponašanju u svrhu samozaštite kada se radi sa životinjama vrlo bitna u prevenciji zoonoza. Ovaj članak sadrži analizu uobičajenih zoonoza u domaćih preživača u jugoistočnoj Europi koje se prenose radeći sa životinjama te načina njihovog prenošenja na ljude. Osviještenost djelatnika o sigurnosti zaštite od zoonoza u proizvodnji preživača odnosi se na stavove i ponašanje zaposlenika u svezi zdravlja i sigurnosti, što isto tako ima znatan učinak na prevenciju zoonoze. Ujedno se raspravlja o povećanju osviještenosti djelatnika o sigurnosti zaštite od zoonoza među djelatnicima u stočarskom sektoru i ponašanjima radnika koja sprječavaju rizike od zoonoza.
Bibliografija: 17 jed.
Summary ; Sažetak.
Keywords: Životinje -- Farme -- Zaštita zdravlja -- Zaštita na radu -- Zoonoze -- Zarazne bolesti -- Patogeni